2014
DOI: 10.1038/bjc.2014.305
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment neutrophil-to-lymphocyte ratio as predictor of adverse outcomes in patients undergoing radical cystectomy for urothelial carcinoma of the bladder

Abstract: Background:An elevated neutrophil-to-lymphocyte ratio (NLR) is associated with poor outcome in various tumours. Its prognostic utility in patients with urothelial carcinoma of the bladder (UCB) undergoing radical cystectomy (RC) is yet to be fully elucidated.Methods:A cohort of patients undergoing RC for UCB in a tertiary referral centre between 1992 and 2012 was analysed. Neutrophil-to-lymphocyte ratio was computed using complete blood counts performed pre-RC, or before neo-adjuvant chemotherapy where applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 26 publications
2
93
0
Order By: Relevance
“…The prognostic role of the pretreatment NLR regarding RFS, PFS and disease-specific survival/cancer-specific survival (DSS/CSS) in bladder cancer patients was evaluated in 9, 7 and 9 studies, respectively. Of the 21 included studies, Hermanns’s study reported adjusted HRs and 95% CIs [29], while 3 studies reported HRs and 95% CIs derived only from a univariate analysis [42, 44, 45]; the remaining studies presented HRs and 95% CIs obtained by a multivariate analysis. With regard to the quality assessment of the included studies, the Newcastle-Ottawa Scale (NOS) scores ranged from 6 to 8.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic role of the pretreatment NLR regarding RFS, PFS and disease-specific survival/cancer-specific survival (DSS/CSS) in bladder cancer patients was evaluated in 9, 7 and 9 studies, respectively. Of the 21 included studies, Hermanns’s study reported adjusted HRs and 95% CIs [29], while 3 studies reported HRs and 95% CIs derived only from a univariate analysis [42, 44, 45]; the remaining studies presented HRs and 95% CIs obtained by a multivariate analysis. With regard to the quality assessment of the included studies, the Newcastle-Ottawa Scale (NOS) scores ranged from 6 to 8.…”
Section: Resultsmentioning
confidence: 99%
“…Patients' background. factors, extracellular matrix-modifying enzymes (which can facilitate invasion and metastasis), and inductive signals (25,26). Cho et al reported that patients with an elevated NLR exhibit a relative lymphocyte-mediated immune response to malignancy, thereby worsening their prognosis and increasing the potential for tumor progression (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on patients who underwent radical cystectomy due to invasive bladder tumor, NLR cut-off value was found to be 3,0 and patients with NLR values higher than this had a significantly lower recurrence-free survival (Hermanns et al, 2014) There is a limited number of studies on the relationship between NLR and prostate cancer in the literature (Keizman et al, 2012;Nuhn et al, 2013;Sonpavde et al, 2014;Sumbul et al, 2014). In a study conducted with the participation of 238 patients with castration resistant metastatic prostate cancer, patients with pre-docetaxel treatment NLR values lower than 3 responded better to treatment and had significantly higher total survival compared to patients with NLR values higher than 3 (Nuhn et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been found that increased NLR was associated with poor prognosis and low survival in various cancer types (Sonpavde et al, 2014). In recent years, the relationship between NLR and urological malignancies has been studied and it has been found that NLR was associated with poor prognosis in renal, bladder and castration resistant prostate cancer as well as other cancer types (Cetin et al, 2013;Sonpavde et al, 2014;Hermanns et al, 2014). It is reported that NLR can predict benigh prostate hyperplasia progression (Tanik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%